Beyond magic traits: Multimodal mating cues in Heliconius butterflies. (1st November 2015) - Mérot, Claire; Frérot, Brigitte; Leppik, Ene; Joron, Mathieu
Abstract: Species coexistence involves the evolution of reproductive barriers opposing gene flow. Heliconius butterflies display colorful patterns affecting mate choice and survival through warning signaling and mimicry. These patterns are called "magic traits" for speciation because divergent natural selection may promote mimicry shifts in pattern whose role as mating cue facilitates reproductive isolation. By contrast, between comimetic species, natural selection promotes pattern convergence. We addressed whether visual convergence interferes with reproductive isolation by testing for sexual isolation between two closely related species with similar patterns, H. timareta thelxinoe and H. melpomene amaryllis . Experiments with models confirmed visual attraction based on wing phenotype, leading to indiscriminate approach. Nevertheless, mate choice experiments showed assortative mating. Monitoring male behavior toward live females revealed asymmetry in male preference, H. melpomene males courting both species equally while H. timareta males strongly preferred conspecifics. Experiments with hybrid males suggested an important genetic component for such asymmetry. Behavioral observations support a key role for short‐distance cues in determining male choice in H. timareta . Scents extracts from wings and genitalia revealed interspecific divergence in chemical signatures, and hybrid female scent composition was significantly associated with courtship intensity by H. timareta males, providing candidate chemical mating cues involved in sexual isolation.